2003
DOI: 10.1002/tox.10131
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride contamination of aquifers in the southeast subhumid pampa, Argentina

Abstract: A diagnostic survey was carried out of the groundwater in the southeast subhumid pampa of Argentina in order to determine the presence, spatial distribution, and concentration of fluoride. The area studied extends along the southeastern border of the pampa plains between latitude 38 degrees 18' and 38 degrees 58' S and longitude 60 degrees 43' and 61 degrees 43' W, covering an irregular surface area of approximately 6000 km2. The region has a large rural and suburban population that relies on this groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Arsenate, on the other hand, is toxic and carcinogenic. Health problems related to its toxicity have been recognized in many regions, including Mexico, Argentina, and Chile [3,4]. It is well known that the mobilization of phosphate and arsenate in the environment is significantly influenced by mineral surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenate, on the other hand, is toxic and carcinogenic. Health problems related to its toxicity have been recognized in many regions, including Mexico, Argentina, and Chile [3,4]. It is well known that the mobilization of phosphate and arsenate in the environment is significantly influenced by mineral surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…On goethite, which has been used extensively in adsorption studies because it is the most widespread crystalline iron oxide in soils and sediments, the adsorption of phosphate and arsenate is rather similar under equilibrium or near equilibrium conditions. Gao and Mucci [10], for example, showed that both species have a strong affinity for the goethite surface in 0.7 M NaCl solution in an ample pH interval (3)(4)(5)(6)(7)(8)(9)(10). The adsorption is high and nearly constant between pH 3 and 7, and then decreases slightly as the pH increases.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been detected fetal abnormalities and abortions in women living in areas of fluorosis . In recent years, researchers found in southern Argentina sources of water and vegetables with high fluoride content, associated with dental fluorosis and decreased pregnancy in cattle and red deer . There are no studies that evaluate the amount of fluoride ingested by grazing animals eating vegetables grown in areas with high F content in soil.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about 200 million people worldwide are supplied with water containing high concentrations of F − (Edmunds and Smedley, 2004). Some of the countries where high contents of F − in groundwater used for drinking have been reported are India (Ramamohana Rao et al, 1993;Karthikeyan et al, 1996;Viswanathan et al, 2009), Serbia (Mandinic et al, 2010), Korea (Chae et al, 2007), China (Zhang et al, 2003;Binbin et al, 2005), Cameroon (Fantong et al, 2010), Nigeria (Gbadebo, 2012), Pakistan (Shah and Danishwar, 2003), Spain (Sanz Pérez and Sanz, 1999), Italy (D'Alessandro et al, 2008), Portugal (Cordeiro et al, 2012), Mexico (Grimaldo et al, 1995), Chile (Mella et al, 1994), Brazil (De Souza et al, 2013), Argentina (Kruse and Ainchil, 2003;Paoloni et al, 2003), etc.…”
Section: Introductionmentioning
confidence: 96%